(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the policy of developed countries in the process of Congo’s independence and Uzbekistan’s diplomatic relations with the SSR, following the feelings of friendship and brotherhood towards the Congolese people and helping them with food products.